Identification and spatial distribution of bioactive compounds in seeds Vigna unguiculata (L.) Walp. by laser microscopy and tandem mass spectrometry - Razgonova, Mayya P.; Burlyaeva, Marina O.; Zinchenko, Yulia N.; Krylova, Ekaterina A.; Chunikhina, Olga A.; Ivanova, Natalia M.; Zakharenko, Alexander M.; Golokhvast, Kirill S. (Plants)
The research presents a comparative metabolomic study of extracts of Vigna unguiculata seed samples from the collection of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources. Analyzed samples related to different areas of use in agricultural production, belonging to different cultivar groups sesquipedalis (vegetable accessions) and unguiculata (grain accessions). Metabolome analysis was performed by liquid chromatography combined with ion trap mass spectrometry. Substances were localized in seeds using confocal and laser microscopy. As a result, 49 bioactive compounds were identified: flavonols, flavones, flavan-3-ols, anthocyanidin, phenolic acids, amino acids, monocarboxylic acids, aminobenzoic acids, fatty acids, lignans, carotenoid, sapogenins, steroids, etc. Steroidal alkaloids were identified in V. unguiculata seeds for the first time. The seed coat (palisade epidermis and parenchyma) is the richest in phenolic compounds. Comparison of seeds of varieties of different directions of use in terms of the number of bioactive substances identified revealed a significant superiority of vegetable accessions over grain ones in this indicator, 36 compounds were found in samples from cultivar group sesquipedalis, and 24 in unguiculata. The greatest variety of bioactive compounds was found in the vegetable accession k-640 from China.